The Knights of the Round Table: Stories of King Arthur and the Holy Grail - Frost, William Henry, 1863-1902; Burleigh, Sydney Richmond, 1853-1931 (Salt Lake City, UT : Project Gutenberg, 2014)
"The Knights of the Round Table: Stories of King Arthur and the Holy Grail" by William Henry Frost is a historical collection of tales written in the late 19th century. The book reimagines and retells classic Arthurian legends, focusing on iconic figures such as King Arthur, Guinevere, and notable knights like Lancelot and Gawain as they embark on various adventures. It appeals to readers who enjoy chivalric stories and the themes of honor, loyalty, and the quest for the Holy Grail. The opening of the book introduces the reader to Glastonbury Tor, where the narrator, accompanied by Helen and her mother, reminisces about the legendary tales surrounding King Arthur. They explore Glastonbury and its historical significance, discussing figures like Joseph of Arimathea and the connection to Avalon. The passage sets the stage for a blend of travel narrative and mythic storytelling, capturing the enchantment of Arthurian lore while hinting at the adventures that will unfold as the characters delve deeper into the world of Camelot and its knights. (This is an automatically generated summary.)
Release date is 2014-07-02
Produced by Al Haines
Keywords: Children's stories; Kings and rulers -- Juvenile fiction; Chivalry -- Juvenile fiction; Knights and knighthood -- Juvenile fiction; Arthur, King -- Juvenile fiction; Secret societies -- Juvenile fiction